Finance and Development, December 1995. (Finance and Development; Finance and Development, 1995)
WHAT early warning signals should policymakers heed to avoid a repeat of a Mexico-type reversal of private capital flows? Experience suggests that a combination of indicators can provide powerful hints of approaching problems.